On the integration and standardization of medication error data: taxonomies, terminologies, causes and contributing factors - Taib, Ibrahim Adham; McIntosh, Andrew Stuart (SAGE Publications, 2010)
Objective: A reliable database on the causes and contributing factors of medication errors can inform strategies for their prevention. To form a single database from multiple databases requires a process of integration that both maximizes the utility of the new data and minimizes the loss of information. Unfortunately, the terminologies used by different studies and databases may limit integration; therefore, terminologies must be standardized prior to integration. Methods: The National Coordinating Council for Medication Error Reporting and Prevention (NCC MERP) Taxonomy of Medication Errors was applied to standardize the different terminologies in 11 studies that reported the causes or contributing factors of medication errors. Results: After standardization, 57% of the reported causes and contributing factors were integrated to form a database while 43% were not integrated because the terminologies could not be standardized or were not similar to the taxonomy. Conclusions: This study highlights the challenges to standardizing and integrating databases and the importance of adopting and applying a standardized terminology to record medical errors.